DEMONSTRATION OF THE EXISTENCE OF THERMAL SURFACE ENERGY AND ITS IMPACTS - A. Titov; I. Malinovsky (European Scientific Journal, ESJ, 2013)
﻿Using variation principle, we have demonstrated experimentally, for the first time, the existence of the thermal surface energy (TSE), resulting from the oriented motion of charged particles inside a material artefact and the energy of the guided electromagnetic (EM) field, which always accompanies the irregular motion of charged particles. The TSE arises gradually as an evolution process of hysteresis type as a result of interaction of the external EM field, characterized by a mean nonzero value of the Poynting vector, with an ensemble of charged particles of material artefact. It has been demonstrated experimentally that the principle of superposition of the external EM fields is not valid in case of TSE, and an artefact is shown to be in a continuous thermal evolution process, which has no symmetry in space and is irreversible in time, clearly confirming the preceding theoretical results of (Dicke 1954). Such process can be called as thermal synthesis. It is shown that the number of influence parameters, necessary for the description of the thermal evolution process is always huge, thus presenting an experimental confirmation of the fundamental theoretical observation of (Stroud et al. 1972, p.1096). We have shown experimentally for the first time that in a homogeneous material a heat source induces a larger flux of energy in a specified direction, if the energy flux in that direction has been created before by an auxiliary heat source. A deep agreement of our studies with Ancient Indian and Greek Philosophies, as well as with the classical German dialectics is outlined.